Mean Antarctic Circumpolar Current transport measured in Drake Passage. Issue 22 (21st November 2016) - Donohue, K. A.; Tracey, K. L.; Watts, D. R.; Chidichimo, M. P.; Chereskin, T. K.
Abstract: The Antarctic Circumpolar Current is an important component of the global climate system connecting the major ocean basins as it flows eastward around Antarctica, yet due to the paucity of data, it remains unclear how much water is transported by the current. Between 2007 and 2011 flow through Drake Passage was continuously monitored with a line of moored instrumentation with unprecedented horizontal and temporal resolution. Annual mean near‐bottom currents are remarkably stable from year to year. The mean depth‐independent or barotropic transport, determined from the near‐bottom current meter records, was 45.6 sverdrup (Sv) with an uncertainty of 8.9 Sv. Summing the mean barotropic transport with the mean baroclinic transport relative to zero at the seafloor of 127.7 Sv gives a total transport through Drake Passage of 173.3 Sv. This new measurement is 30% larger than the canonical value often used as the benchmark for global circulation and climate models. Key Points: A moored array measured bottom currents across Drake Passage with unprecedented resolution The mean barotropic Antarctic Circumpolar transport is 45.6 Sv ± 8.9 Sv The ACC transport of 173.3 Sv is 30% larger than the canonical value of 134 Sv